DEVELOPMENT OF MODEL OF CREDIT DISTRIBUTION FOR SMEs TO ANTICIPATE THE DEVELOPMENT OF INFORMAL FINANCIAL INSTITUTIONS (Case Study: In SMEs in Deli Serdang District) - Julita Julita, S.E., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
The classic problem that cannot be denied and that continually plagued some Small and Medium Enterprises (SMEs), is the problem of capital, which resulted in not maximally expected goals. Some qualified SMEs can use Banking services to meet their business capital needs and not many SMEs also uses informal financial institutions in this case are moneylender services for their business capital, although we know that the set interest rate is relatively higher than Bank, but because the procedures and requirements are easier then some SME actors use informal financial institutions or moneylender service. This study aims to provide input and development of the most relevant credit channel model that can assist some SMEs in fulfilling their business capital in Deli Serdang Regency, and it is expected that the government and other stakeholders should focus on solving the problem. However, the SME sector is one of the supporters of economic growth in an area, especially in Deli Serdang Regency. This research uses Research and Development (R & D) method. Data collection techniques in general using field study with the dissemination of the instrument (questionnaire) research to the sample in this case SMEs in Deli Serdang District. Data analysis Research instruments that have been collected will be analyzed using descriptive analysis method. Of the only 70 entrepreneurs who were respondents, only 10.9% believed that the capital owned was sufficient to develop the business, 64.6% said they still need an injection even though they have and 24.6%, even said the capital injection is a very urgent need for the sake of continuity of his business.